2021
DOI: 10.1590/1807-1929/agriambi.v25n2p96-100
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria inoculation in maize associated with nitrogen and zinc fertilization at sowing

Abstract: Rhizobacteria have a wide range of plant growth-promoting mechanisms of action, making them an alternative and/or complementary biological input for chemical fertilizers. In this respect, the present study aimed to assess growth and nitrogen accumulation in maize plants as a function of Azospirillum brasilense, Bacillus subtilis, zinc and nitrogen application at sowing. The experiment with the ‘AL Bandeirante’ maize variety was conducted in a greenhouse, using a completely randomized design. The treatments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…In another study, inoculation with A. brasilense and B. subtilis increased the stem diameter and shoot N content of maize plants when N fertilization was not used at the sowing. The authors concluded that the observed increases indicate a synergy between the two microorganism species, demonstrating that, in this case, their combined inoculation in maize reduced the need for N fertilization at sowing (Moreno et al 2021). Combined inoculation of Azospirillum and a P-solubilizer (B. megaterium var.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In another study, inoculation with A. brasilense and B. subtilis increased the stem diameter and shoot N content of maize plants when N fertilization was not used at the sowing. The authors concluded that the observed increases indicate a synergy between the two microorganism species, demonstrating that, in this case, their combined inoculation in maize reduced the need for N fertilization at sowing (Moreno et al 2021). Combined inoculation of Azospirillum and a P-solubilizer (B. megaterium var.…”
Section: Discussionmentioning
confidence: 95%
“…Genes involved in the production of low molecular weight organic acids, P and N metabolism were identi ed in the genome of Bacillus strains (Velloso et al 2020) and they have also been described as bene cial to plant growth for their e ciency in phosphate solubilization and organic acid production (Gomes et al 2014;Abreu et al 2017;Ribeiro et al 2018). In addition, relevant results regarding Azospirillum co-inoculated with different bacterial species have been described in the literature (Gómez-Godínez et al 2019; Moretti et al 2020;Rondina et al 2020;Moreno et al 2021). There is an increasing adoption of the co-inoculation of Azospirillum and Bradyrhizobium by soybean farmers in Brazil over the last years.…”
Section: Introductionmentioning
confidence: 99%
“…ANDREOTE, 2016). The microorganism-plant interaction can promote the growth of living organisms in the system and intensify the plants' tolerance to biotic and abiotic stresses (MORENO et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show the beneficial effects of multifunctional microorganisms in increasing shoot dry biomass and productivity of soybean (SILVA et al, 2020b;CHAGAS JUNIOR et al, 2022) and common bean (Phaseoulus vulgaris) (REZENDE et al, 2021a); growth promotion of rice (Oryza sativa L.) (FERNANDES et al, 2021;PARRALES et al, 2022) and accumulation of N in maize plants (Zea mays) (MORENO et al, 2021). In addition, the use of different beneficial microorganisms at the same time, defined as coinoculation or consortium of microorganisms, has been gaining market share, since it adds different mechanisms of action, producing potential synergistic effects, compared to the use of isolated microorganisms (FLAUZINO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they hypothesized that bio lm formation induced by root exudates in Bacillus and Azospirillum forming aggregates may provide favorable nitrogen-xing conditions by protecting bacteria from oxygen, or the consortia may provide nutrients that stimulate Azospirillum nitrogen xation.In another study, inoculation with A. brasilense and B. subtilis increased the stem diameter and shoot N content of maize plants when N fertilization was not used at the sowing. The authors concluded that the observed increases indicate a synergy between the two microorganism species, demonstrating that, in this case, their combined inoculation in maize reduced the need for N fertilization at sowing(Moreno et al 2021). Combined inoculation of Azospirillum and a P-solubilizer (B. megaterium var.…”
mentioning
confidence: 96%